Sehat Bersama Desa: Edukasi Gizi dan Pola Hidup Bersih untuk Keluarga Studi Dusun Borok Lelet Desa Kotaraja - Rahadi, Bayu; Zulma, Husein (Lembaga Publikasi Ilmiah Nusantara, 2025)
The Healthy Together Village Program is a community service initiative focused on increasing families’ understanding of the importance of balanced nutrition and the implementation of clean living habits in daily life. This activity was carried out in Borok Lelet Hamlet, Kotaraja Village, in response to initial findings indicating low community knowledge regarding the selection of nutritious food ingredients, healthy eating patterns, as well as environmental cleanliness and personal hygiene practices. The main goal of this program is to provide practical and easily applicable education for families, thereby encouraging behavioral changes toward a healthier lifestyle. The implementation methods include environmental observation, interactive counseling, demonstrations on selecting food ingredients and simple food processing, as well as handwashing practices and household sanitation. Evaluation was conducted through pre-tests and post-tests to measure the improvement in participants’ knowledge. The results show a significant increase in community understanding, particularly in the application of balanced nutritious menus, the importance of clean water and sanitation, and healthy and hygienic habits within families. Additionally, active community participation indicates that the education provided is relevant to local needs and can be independently implemented. This program is expected to serve as a sustainable model for villages in efforts to improve family health quality and create a cleaner and healthier environment.